Persepsi Masyarakat Lokal terhadap Pengembangan Potensi Wilayah Pesisir untuk Meningkatkan Ekonomi - Wardani Bakri Katti, Siti; Agus Mokodompit, Eliyanti (LP3M, Universitas Muhammadiyah Kendari, 2025)
This study aims to examine local community perceptions of coastal potential development in Tanjung Bira, South Sulawesi, and its impact on economic growth in 2024. Coastal areas play a crucial role in supporting the regional economy through tourism, fisheries, and micro-enterprises. However, the success of such development largely depends on community support and involvement. Success indicators can be measured through the level of acceptance and participation of the local population, economic growth driven by key sectors, and changes in social welfare. Additionally, environmental sustainability, including coastal ecosystem preservation and natural resource management, as well as infrastructure improvements to enhance accessibility and economic activities, are key factors in assessing the development's impact. This study employs a qualitative approach using in-depth interviews, observations, and document analysis. The respondents include 150 individuals, comprising fishermen, tourism business operators, and the general public. The findings indicate that 75% of the community holds a positive view of coastal development, particularly in the tourism sector, which is seen as creating job opportunities and increasing income. However, concerns remain regarding environmental impact and socio-cultural changes. Therefore, a participatory and sustainable approach is necessary to ensure that policies not only boost the economy but also preserve the environment and enhance community welfare.